Dynamic changes in kynurenine pathway metabolites in multiple sclerosis: A systematic review - Fathi, Mobina; Vakili, Kimia; Yaghoobpoor, Shirin; Tavasol, Arian; Jazi, Kimia; Mohamadkhani, Ashraf; Klegeris, Andis; McElhinney, Alyssa; Mafi, Zahedeh; Hajiesmaeili, Mohammadreza; Sayehmiri, Fatemeh (Frontiers in Immunology, 2022)
Background: Multiple sclerosis (MS) is a debilitating neurodegenerative disorder characterized by axonal damage, demyelination, and perivascular inflammatory lesions in the white matter of the central nervous system (CNS). Kynurenine pathway (KP), which is the major route of tryptophan (TRP) metabolism, generates a variety of neurotoxic as well as neuroprotective compounds, affecting MS pathology and the severity of impairments. Alterations in KP have been described not only in MS, but also in various psychiatric and neurodegenerative diseases. The purpose of this systematic review is to investigate the previously reported dysregulation of KP and differences in its metabolites and enzymes in patients with MS compared to healthy control subjects. Method: Electronic databases of PubMed, Scopus, Cochrane Database of Systematic Reviews, and Web of Science were searched to identify studies measuring concentrations of KP metabolites and enzymes in MS patients and control subjects. The following metabolites and enzymes implicated in the KP were investigated: TRP, kynurenine (KYN), kynurenic acid (KYNA), quinolinic acid (QUIN), picolinic acid (PIC), hydroxyindoleacetic acid (HIAA), indoleamine 2,3-dioxygenase (IDO), kynurenine aminotransferase (KAT), and their related ratios. Result: Ten studies were included in our systematic review. Our review demonstrates that IDO expression is reduced in the peripheral blood mononuclear cells (PBMCs) of MS patients compared to healthy controls. Also, increased levels of QUIN and QUIN/KYNA in the serum and cerebrospinal fluid (CSF) of MS patients is observed. Differences in levels of other metabolites and enzymes of KP are also reported in some of the reviewed studies, however there are discrepancies among the included reports. Conclusion: The results of this investigation suggest a possible connection between alterations in the levels of KP metabolite or enzymes and MS. QUIN levels in CSF were higher in MS patients than in healthy controls, suggesting that QUIN may be involved in the pathogenesis of MS. The data indicate that differences in the serum/blood or CSF levels of certain KP metabolites and enzymes could potentially be used to differentiate between MS patients and control subjects.